An Evaluation of the Initial Year of Zero-Base Budgeting in the Federal Government - Sherlekar, Virendra S.; Dean, Burton V. (Management Science, 1980)
This paper presents a comprehensive evaluation of the strengths and weaknesses of the Zero-Base Budgeting (ZBB) process during the initial year of its implementation in the Federal Government. The evaluation includes ten Departments and six agencies of the Federal Government representing 74 percent of the total budget authority of 560 billion dollars. It is based on the information received in responses from federal agencies to the Office of Management and Budget Eleven major criteria were formulated for use in evaluating the applicability of the ZBB process and its performance in the individual agencies. A scoring model was used to determine the effectiveness of the ZBB process within each agency, as well as across agencies. ZBB was perceived by federal agencies as an effective tool for use in the allocation of limited resources. The following aspects of ZBB were ranked in the order in which they yield the greatest benefits in producing effective budgets: (a) priority ranking of agency programs, (b) participation of management in decisionmaking, and (c) conducting trade-offs within and across programs. In most cases, the increased participation (extent and quality) resulted in the establishment of a close link with top management and an enhanced understanding of organizational objectives, priorities, and resource allocations to various programs. The use of ZBB was not intended to and did not, in fact, produce significant tangible cost savings in federal agency 1979 budgets, but did result in reallocations of resources to activities with higher priority. Most federal agencies believed that the use of ZBB required excessive expenditures of time and effort. The agencies felt that ZBB was not particularly applicable to “uncontrollable” programs and hence the time and effort spent on using ZBB in these decision units was not beneficial. The agencies faced problems in developing “minimum level” packages which represent lowest level budgets for the organizational units. Most agencies used an arbitrary percentage reduction from the existing level to force uniformity across all decision units. Use of a predefined “minimum level” may have precluded a zero-base analysis of the decision units which is the major cornerstone of ZBB. Priority ranking of decision packages at the subordinate management level was usually carried out by managers using their own independent judgments. At the top agency level, most agencies used formal ranking procedures and collegial panels to produce the initial ranking of agency-wide decision packages. The difficulties agencies faced in determining priorities of the decision packages included ranking those functions/activities that were dissimilar and/or interrelated and considering those activities not having measurable outputs or distinct workload measures.